Patent landscape analysis—Contributing to the identification of technology trends and informing research and innovation funding policy - Tomas vanRijn; James Kenneth Timmis (Microbial Biotechnology, 2023)
Abstract Patents and the systematic analysis thereof provide important decision information for a range of stakeholders pursuing diverse goals. However, in particular academia and small‐scale private sector innovators underappreciate the value of patent information for identifying research gaps, ensuring originality of their work and, in turn, maximisation of limited (public) funds. By the same token, pertinent public sector organisations, such as regulators, require overviews of potentially upcoming technologies to adequately adapt regulatory protocols. The latter, in particular if contemporary scientific evidence is not sufficient, can require a substantial amount of time and lead to a delay in the marketing of important innovations. Patent landscape analysis (PLA) is a very useful method to create overviews of technology fields and thereby indicate if, inter alia, a specific line of scientific enquiry and its application have already been pursued or potential regulatory gaps will exist in the near‐ to mid‐term future. The objective of this communication is to increase awareness of the utility of patent information and provide support in retrieval and analysis of pertinent information for those involved in biotech R&D. Based on Espacenet, a patent search engine, we provide basic guidance on search strategy development, piloting and execution, and data preparation and analysis. To highlight the value of PLA, we also summarise selected results of a PLA we performed recently for microbiome targeting interventions, also referred to as live biotherapeutic products.